2011
DOI: 10.1007/978-3-642-28720-6_198
|View full text |Cite
|
Sign up to set email alerts
|

What is in that Drink: The Biological Actions of Ethanol, Acetaldehyde, and Salsolinol

Abstract: Alcohol abuse and alcoholism represent substantial problems that affect a large portion of individuals throughout the world. Extensive research continues to be conducted in an effort to identify the biological basis of the reinforcing properties of alcohol in order to develop effective pharmacotherapeutic and behavioral interventions. One theory that has developed within the alcohol field over the past 4 decades postulates that the reinforcing properties of alcohol are due to the action of the metabolites/prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 125 publications
(140 reference statements)
1
14
0
Order By: Relevance
“…All are well known antipsychotic drugs. The metabolites with the largest MCS (6 heavy atoms) are salsoline and salsolinol (which is not unreasonable, as they are condensation products of dopamine and acetaldehyde [8387]). When this ‘whole-ring’ assumption is relaxed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All are well known antipsychotic drugs. The metabolites with the largest MCS (6 heavy atoms) are salsoline and salsolinol (which is not unreasonable, as they are condensation products of dopamine and acetaldehyde [8387]). When this ‘whole-ring’ assumption is relaxed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…; Deehan et al . ). Furthermore, salsolinol stimulates firing rate of DA neurons ex vivo (Xie & Ye ; Xie et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Hipólito et al . ; Deehan, Brodie & Rodd ). Indeed, brain salsolinol quantification following in vivo ethanol administration is still an unresolved issue (Lee et al .…”
Section: Introductionmentioning
confidence: 99%
“…The possible involvement of the ethanol metabolite acetaldehyde as a mediator of the reinforcing effects of ethanol was proposed over 40 years ago, and the ‘acetaldehyde hypothesis’ has been strengthened since then (reviewed by Correa et al . ; Deehan, Brodie & Rodd ). Studies in the late 1970s (Brown, Amit & Rockman ) showed that naïve rats maintained in operant chambers self‐administer acetaldehyde solutions into the cerebral ventricles.…”
Section: Introductionmentioning
confidence: 99%
“…; Deehan et al . ) demonstrated that rats selectively bred as alcohol drinkers (strain P of Indianapolis) placed in operant chambers self‐administer both ethanol and acetaldehyde into the brain ventral tegmental area (VTA). Most importantly, the reinforcing concentrations of acetaldehyde [(6–12) × 10 −6 M] are three orders of magnitude lower than those required for ethanol (17 × 10 −3 M) (Oster et al .…”
Section: Introductionmentioning
confidence: 99%